Universal access through inclusive instructional design : international perspectives on UDL - Gronseth, Susie L.; Dalton, Elizabeth M. (New York : Routledge, Taylor & Francis Group, 2020)
"Universal Access Through Inclusive Instructional Design explores the ways that educators around the world reduce barriers for students with disabilities and other challenges by planning and implementing accessible, equitable, high-quality curricula. Incorporating key frameworks such as Universal Design for Learning, these dynamic contributions highlight essential supports for flexibility in student engagement, representation of content, and learner action and expression. This comprehensive resource--rich with coverage of foundations, policies, technology applications, accessibility challenges, case studies, and more--leads the way to design and delivery of instruction that meets the needs of learners in varying contexts, from early childhood through adulthood"--
UDL and connected laws, theories, and frameworks / Elizabeth M. Dalton -- Conceptual frameworks for design and accessibility : the design of an online learning system / Nantanoot Suwannawut -- Snapshot: Intersections of race, disability, class, and gender in special/inclusive education : the case of Sweden / Girma Berhanu -- Snapshot: Proactive design to ensure accessibility / Lesley Casarez, David Hooks, Gina Shipley, and Dallas Swafford -- The prospects of universal design for learning in South Africa to facilitate the inclusion of all learners / Marcia Lyner-Cleophas -- The global UDL virtual classroom : a model for international collaboration and learning / Frances Smith and Serra De Arment -- Decaffeinated UDL : Chile in quest of inclusive education / Boris Alvarez, Paola Andrea Vergara, and Irma Iglesias -- Universal design for learning in China / Haoyue Zhang and George Zhao -- Snapshot: Reducing learning barriers through the use of FACE Program / Radhike Khanna and Elizabeth M. Dalton -- Snapshot: A district's journey to measure Universal Design for Learning (UDL) / Katie Novak and Laura Chesson -- Access to the curriculum for students with disabilities; moving closer to the promise of UDL in inclusive U.S. Classrooms / Rita Brusca-Vega and Anastasia Trekles -- Balancing requirements, options and choice in UDL : smorgasbord or nutritious diet? / Britt Tatman Ferguson -- UDL practices in India : paving a path from equality to equity in learning / Aashna Khurana -- UDL-inspired pedagogical practices and a case study in regular Japanese classes / Kiyoji Koreeda -- No-tech solutions for utilizing the UDL framework in the inclusive mathematics classroom / Marla J. Lohmann, Ruby L. Owiny, Kathleen A. Boothe -- Snapshot: Science for all through UDL : using UDL as a framework for science education for the English learner / Heather Pacheco-Guffrey, Jeanne Carey Ingle -- Snapshot: Reconstructing asynchronous online learning with UDL / Kathryn Nieves -- SAMR strategies for the integration of technology through UDL / Debra K. Bauder, Katherine M. Cooper, and Thomas J. Simmons -- Engagement, representation, and expression in online mind mapping activities / Rosa Cendros Araujo and George Gadanidis -- Handcrafted customized content and school activities with newly developed technologies / Shigeru Ikuta and Yumi Hisatsune -- Connecting the world in a disconnected classroom / Vivian B. Intatano -- Snapshot: Wearable assistive technology : an illuminated glove project with conductive thread and LilyPad technology / Cindy L. Anderson and Kevin M. Anderson -- Snapshot: Aquatic adventures : deep dive investigation of UDL through a pond keepers project / Juliet Boone -- Universal access in online distance education : a case study from the Philippines / Melinda dela Peña Bandalaria -- Applying UDL principles in an inclusive design project based on MOOCs reviews / Francisco Iniesto, Covadonga Rodrigo, and Garron Hillaire -- General accessibility guidelines for online course content creation / Kathleen Bastedo and Nancy Swenson -- Snapshot: Creating UDL learning and teaching strategies to address the underrepresentation of present-day indigenous perspectives / Kerry Armstrong, Brenda Boreham, and Terri Mack -- Snapshot: Using the YouTube automated captioning tool for video lectures / Sandra A. Rogers -- Snapshot: A fully mobile professional development course for teachers in Israel / Shir Boim Shwartz and Eran Adi Cioban -- Examining the integration of digital and multimodal resources in online courses using a universal design framework / Peggy Semingson and Kathryn Pole -- The intersection of Chinese philosophical traditions and UDL : exploring current practice in Chinese early childhood classrooms / Janet Arndt and Nili Luo -- Promoting inclusion education and intercultural competence in an Ecuadorian international service learning project-based course / Maria DeFreece Lawrence -- Designing an online graduate orientation program : informed by UDL and studied by design-based research / Jennifer Lock, Carol Johnson, Jane Hanson, Yang Liu, and Alicia Adlington -- Developing inclusive education in Ireland : the case for UDL in initial teacher education / Ellen Reynor -- Snapshot: Understanding how UDL can serve as a framework for instructional decisions / Lisa Harris and Lindsay Yearta -- Snapshot: Importance of classroom atmosphere in elementary schools to improve the inclusive education system in Japan / Honami Okabe and Masayoshi Tsuge -- Innovative approach : using Legos in a hands-on activity to teach educators the foundations of UDL / Amir Bar and Betty Shrieber -- Spreading the word about assistive technology and universal design for learning : a model for professional teacher learning / Jennifer Edge-Savage and Mike Marotta -- Universal design for learning in augmented and virtual reality trainings / Katharina Menke, Jennifer Beckmann, and Peter Weber -- Raising the bar with UDL : a case for change / Leanne Woodley -- Snapshot: Designing for open educational environments : balancing access, equity, and engagement / Elizabeth Childs and Jo Axe -- Snapshot: Support for students with developmental disabilities in a regular elementary school class in Japan / Shintaro Nagayama and Masayoshi Tsuge -- The potential evolution of Universal Design for Learning (UDL) through the lens of technology innovation / David Banes and Kirk Behnke -- Universal design for learning and the landfill of revolutionary educational innovations / Dave L. Edyburn -- Snapshot: The precarious promise of emergent tech and universal design for learning : a pivotal point / Susan Molnar -- Snapshot: A vision for pre-service and in-service learner-centered teaching through the arts / Susan Trostle Brand and Laurie J. DeRosa -- Epilogue: Learning from diverse perspectives on inclusive instructional design and next steps / Susie L. Gronseth.
Includes bibliographical references and index.
Keywords: Inclusive education -- Case studies; Individualized instruction -- Case studies; Instructional systems -- Design -- Case studies; Educational technology -- Case studies; Universal design -- Case studies